2019
DOI: 10.3389/fimmu.2019.00296
|View full text |Cite
|
Sign up to set email alerts
|

Congenital Defects in Actin Dynamics of Germinal Center B Cells

Abstract: The germinal center (GC) is a transient anatomical structure formed during the adaptive immune response that leads to antibody affinity maturation and serological memory. Recent works using two-photon microscopy reveals that the GC is a highly dynamic structure and GC B cells are highly motile. An efficient selection of high affinity B cells clones within the GC crucially relies on the interplay of proliferation, genome editing, cell-cell interaction, and migration. All these processes require actin cytoskelet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 114 publications
1
12
1
Order By: Relevance
“…We previously showed that the Rac GAP ARHGAP25 plays an important role in hematopoietic stem and progenitor cell (HSPC) mobilization, in part by strengthening signaling through the CXCL12-CXCR4 axis to promote HSPC retention in the bone marrow niche (21). Whereas it has previously been shown that Rho family GTPases act on B cell development through actin-mediated pathways (22), here we demonstrate that Arhgap25 plays an important role in terminal B cell differentiation and B cell activation by influencing CXCL12-CXCR4 signaling.…”
Section: Introductioncontrasting
confidence: 67%
“…We previously showed that the Rac GAP ARHGAP25 plays an important role in hematopoietic stem and progenitor cell (HSPC) mobilization, in part by strengthening signaling through the CXCL12-CXCR4 axis to promote HSPC retention in the bone marrow niche (21). Whereas it has previously been shown that Rho family GTPases act on B cell development through actin-mediated pathways (22), here we demonstrate that Arhgap25 plays an important role in terminal B cell differentiation and B cell activation by influencing CXCL12-CXCR4 signaling.…”
Section: Introductioncontrasting
confidence: 67%
“…CDC42 controls the multilineage development of blood progenitors and their egress from the bone marrow to the periphery, influences the tight balance between myelopoiesis and erythropoiesis (16,17), and contributes to the immune system regulation by coordinating survival, proliferation, migration, receptor expression, activation signal transduction, and cytokine secretion in T (18)(19)(20) and B cells (21). Dysregulated CDC42-dependent actin dynamics may, therefore, impede multiple stages of B cell development and affinity maturation, resulting in an aberrant germinal center response and immunodeficiency, autoimmunity, and lymphoproliferation (22).…”
Section: Discussionmentioning
confidence: 99%
“…These DNA repair pathways are error prone and introduce nucleotide exchange and additional nucleotide mutations during the repair of the V segment, diversifying the BCR. Affinity maturation through SHM is important for development of the robust immune response to pathogens, as highlighted in the many PID that affect the GC response leading to aberrant B cell antibody responses (37). For instance, patients lacking AID or UNG activity and therefore SHM, develop hyper IgM syndrome and are prone to severe bacterial infections (38).…”
Section: Somatic Hypermutation and Germinal Center Responsementioning
confidence: 99%